Peningkatan Hasil Belajar IPAS melalui Model Pembelajaran Inquiri Terbimbing pada Kelas V SDN 31 Cakranegara - Azzahra, Hanum Aulia; Hidayati, Vivi Rachmatul; Susilamurni, Baiq Sri (Mataram University, 2025)
This study was conducted to improve students’ learning outcomes in Science and Social Studies (IPAS) through the implementation of the Guided Inquiry Learning model in Grade V at SDN 31 Cakranegara. This research employed a Classroom Action Research (CAR) design involving 31 students as the research subjects. The method used in this study was descriptive, with data collected through tests and observations. The results showed that 21 students achieved mastery in the first cycle and 28 students in the second cycle. The classical learning mastery in the first cycle reached 67.7% with an average absorption rate of 60.9%, while in the second cycle, mastery increased to 90.3% with an absorption rate of 89.6%. Based on these findings, it can be concluded that the application of the Guided Inquiry Learning model effectively improved the IPAS learning outcomes of Grade V students at SDN 31 Cakranegara.